Risk factors for loss of skeletal muscle mass in patients with cirrhosis. Issue 5 (1st February 2019) - Sung, Ji Hyun; Uojima, Haruki; Hidaka, Hisashi; Tanaka, Yoshiaki; Wada, Naohisa; Kubota, Kousuke; Nakazawa, Takahide; Shibuya, Akitaka; Fujikawa, Tomoaki; Yamanoue, Hiroki; Kako, Makoto; Koizumi, Wasaburo
Abstract : Aim: The present study aimed to assess the correlation between loss of skeletal muscle mass (LSMM) and the clinical characteristics of patients with liver cirrhosis. Methods: This multicenter, prospective study was undertaken at five locations in Japan and involved a 12‐month observation period. After baseline assessment, the change in the skeletal muscle index per year (ΔSMI/y) was evaluated in the enrolled patients; LSMM was defined as ΔSMI/y < 0. We evaluated the relationships between LSMM and baseline clinical characteristics in patients with liver cirrhosis. Results: A total of 166 patients with cirrhosis were enrolled and, of these, 123 patients (74.1%) showed LSMM. Multivariate analysis confirmed that hepatic encephalopathy, Wisteria floribunda agglutinin‐positive Mac‐2 binding protein (WFA + ‐M2BP) (≥1.86), age (≥60 years), and grip strength (<18 kg for women and <26 kg for men) were independent predictors of skeletal muscle decline ( P = 0.042, odds ratio [OR] 8.997, 95% confidence interval [CI] 1.083–74.71; P = 0.023, OR 3.970, 95% CI 1.468–6.177; P = 0.037, OR 2.526, 95% CI 1.056–6.045; and P = 0.002, OR 3.970, 95% CI 1.691–9.322, respectively). Conclusions: Advanced age, low grip strength, hepatic encephalopathy, and high WFA + ‐M2BP might be risk factors for LSMM in liver cirrhosis patients.